2021
DOI: 10.3390/soilsystems5040068
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Waterlogging Depresses Early Growth of Sunflower (Helianthus annuus L.) on Saline Soils with a Shallow Water Table in the Coastal Zone of Bangladesh

Abstract: Sunflower (Helianthus annuus L.), which is widely grown globally for its high-quality edible oil, is reasonably salt and drought tolerant but it is susceptible to waterlogging. In the saline coastal zone of the Ganges delta, sunflower is often exposed to sudden heavy rainfall during early growth but plant tolerance to such events is not known. Hence, we evaluated the effect of short-term soil inundation (referred to as waterlogging) for 0, 24, 48 and 72 h on sunflower at emergence, 2-leaf, and 4-leaf stages in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Consequently, the nutrient uptake by plants dramatically decreases, leading to plant starvation [ 7 ]. Several studies have shown that waterlogging is a significant yield-limiting factor for crop yield and growth [ 8 , 9 ]. For instance, waterlogging reduced the yield of corn by about 4.7% each day for up to seven days compared to well-watered corn [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the nutrient uptake by plants dramatically decreases, leading to plant starvation [ 7 ]. Several studies have shown that waterlogging is a significant yield-limiting factor for crop yield and growth [ 8 , 9 ]. For instance, waterlogging reduced the yield of corn by about 4.7% each day for up to seven days compared to well-watered corn [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Root development and growth were clearly affected by WL (Figure 4), and in general, the three species showed a decrease in root biomass. This is a common response in plants, as shown for annual cereals [52,[66][67][68], annual dicot crops [69,70], perennial forage grasses [61,71] and perennial forage legumes [72,73]. Root growth decreases due to a deficiency of oxygen, energy, nutrients and accelerated root senescence [74].…”
Section: Discussionmentioning
confidence: 99%
“…He showed that plant growth is hindered by the combined effect of waterlogging and salinity because of higher concentration of Na+ and Cl-in the shoot. An experiment conducted by Paul et al (2021c) in the south-west coastal region of Bangladesh demonstrated that short term waterlogging more than 24 hours diminished early growth of sunflower.…”
Section: Waterloggingmentioning
confidence: 99%